Lipopolysaccharide (LPS) Aggravates High Glucose- and Hypoxia/Reoxygenation-Induced Injury through Activating ROS-Dependent NLRP3 Inflammasome-Mediated Pyroptosis in H9C2 Cardiomyocytes - Zhen Qiu; Yuhong He; Hao Ming; Shaoqing Lei; Yan Leng; Zhong-yuan Xia (Journal of Diabetes Research)
Diabetes aggravates myocardial ischemia-reperfusion (I/R) injury because of the combination effects of changes in glucose and lipid energy metabolism, oxidative stress, and systemic inflammatory response. Studies have indicated that myocardial I/R may coincide and interact with sepsis and inflammation. However, the role of LPS in hypoxia/reoxygenation (H/R) injury in cardiomyocytes under high glucose conditions is still unclear. Our objective was to examine whether lipopolysaccharide (LPS) could aggravate high glucose- (HG-) and hypoxia/reoxygenation- (H/R-) induced injury by upregulating ROS production to activate NLRP3 inflammasome-mediated pyroptosis in H9C2 cardiomyocytes. H9C2 cardiomyocytes were exposed to HG (30 mM) condition with or without LPS, along with caspase-1 inhibitor (Ac-YVAD-CMK), inflammasome inhibitor (BAY11-7082), ROS scavenger N-acetylcysteine (NAC), or not for 24 h, then subjected to 4 h of hypoxia followed by 2 h of reoxygenation (H/R). The cell viability, lactate dehydrogenase (LDH) release, caspase-1 activity, and intracellular ROS production were detected by using assay kits. The incidence of pyroptosis was detected by calcein-AM/propidium iodide (PI) double staining kit. The concentrations of IL-1β and IL-18 in the supernatants were assessed by ELISA. The mRNA levels of NLRP3, ASC, and caspase-1 were detected by qRT-PCR. The protein levels of NF-κB p65, NLRP3, ASC, cleaved caspase-1 (p10), IL-1β, and IL-18 were detected by western blot. The results indicated that pretreatment LPS with 1 μg/ml not 0.1 μg/ml could efficiently aggravate HG and H/R injury by activating NLRP3 inflammasome to mediate pyroptosis in H9C2 cells, as evidenced by increased LDH release and decreased cell viability in the cells, and increased expression of NLRP3, ASC, cleaved caspase-1 (p10), IL-1β, and IL-18. Meanwhile, Ac-YVAD-CMK, BAY11-7082, or NAC attenuated HG- and H/R-induced H9C2 cell injury with LPS stimulated by reversing the activation of NLRP3 inflammasome-mediated pyroptosis. In conclusion, LPS could increase the sensitivity of H9C2 cells to HG and H/R and aggravated HG- and H/R-induced H9C2 cell injury by promoting ROS production to induce NLRP3 inflammasome-mediated pyroptosis.